The Practice of Account Payable and Receivable in the ShopeePay Later System According to Hanafi and Shafi’i Madzhab - Prasetya, Teguh Eka; Rachmawati, Andini; Nasution, Saipul; Sa’diah, Chindy Halimatus (AL- IKTISAB Journal of Islamic Economic Law, 2024)
One of the services offered by Shopee to consumers is ShopeePay Later. Paylater can be interpreted as a service that provides online or electronic money loans and helps people with instalment methods without credit cards. ShopeePay Later leads to the problem of debt and credit. Allah Swt. allows doing debt and credit or qardh if the qardh goes to something good, such as helping in distress or helping people who are less well off by lending some of their assets, but what distinguishes it is the way it is carried out if a debt is generally done directly. However, ShopeePay Later is online, where the agreement or contract is made indirectly. This research aims to discover the Hanafi and Shafi'i madzhab scholars opinions on the practice of accounts payable contained in the ShopeePay Later online payment site. This research is library research using a descriptive comparative approach, where researchers make a systematic explanation of the views of the Hanafi and the Shafi'i madzhab on the practice of debt and credit contained in the ShopeePay Later online payment site and compare, and then analyse them. The result of this study is the practice of debt and credit contained in the ShopeePay Later application, according to the Hanafi and the Shafi’i madzhab, there are differences in the object of goods returned. According to the view of the Hanafi madzhab scholars what is borrowed by muqtaridh must be returned with the same or mistli, if the goods returned are not the same or mistli then the contract in it is invalid. In contrast, the view of the Shafi'i madzhab is that what is borrowed and what is returned must be of the same or comparable, as long as it does not harm the muqaridh as a debt giver.